Studi empiris terhadap implementasi ilmu tasawuf atas pelaku ekonomi Islam di lingkungan sekitar - Ainiyah, Rizka Nur (Maliki Interdisciplinary Journal, 2023)
Sufism is the embodiment of the ihsan part of Islamic law, which is one of the other three frameworks of Islamic teachings, Faith and Islam. Thus, the concept of Sufism must remain within the framework of the Shari’a. As quoted by al-Qusyairi, "We should not confer sanctity so that they are well aware of their conformity with Sharia law". ihsan’s performance, the servant’s appreciation of his religion, and his potential Great offers spiritual liberation, so he invites people to know his own Weaknesses, finally know his perfect God. In this article, the author will analyze the implementation of Sufism on Islamic economic actors with a focus on tela-tela traders as a case study. The approach used is a qualitative approach in which the author collects data from in-depth interviews with the seller. The implementation of Sufism in Islamic Economic Practices carried out by the mother of the seller is: Ethics in business: Islamic economic actors are very, pay attention to ethics in doing business, such as: patience, honesty, trustworthiness and not harming others. Sincere and Tawakkal: This Islamic economic actor has an awareness that in running a business alone is not only for profit, but also as worship to Allah SWT. The implementation of Sufism in Islamic Economic Practices carried out by the mother of the seller is: Ethics in business: Islamic economic actors are very, pay attention to ethics in doing business, such as: patience, honesty, trustworthiness and not harming others.